2017
DOI: 10.1021/acsami.7b10258
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of Cyclometalated Iridium(III) Complexes: Anti-Metastasis and Lysosome-Damaged Photodynamic Therapy

Abstract: Four phosphorescent cyclometalated iridium(III) complexes containing benzimidazole moiety have been designed and synthesized. These Ir(III) complexes can effectively inhibit several cancerous processes, including cell migration, invasion, colony formation, and angiogenesis. Interestingly, they show a much higher singlet oxygen quantum yield in an acidic solution than in a neutral solution. Upon irradiation at 425 nm with low energy (1.2 J cm), they can induce apoptosis through lysosomal damage, evaluation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 43 publications
1
92
0
1
Order By: Relevance
“…The diffusion of cancer cells is closely related to cell migration, which is significative for studying the effect of complexes on cancer cell antimigration . The effects of complexes 2 and 4 on A549 antimigration were investigated by wound healing migration assays.…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion of cancer cells is closely related to cell migration, which is significative for studying the effect of complexes on cancer cell antimigration . The effects of complexes 2 and 4 on A549 antimigration were investigated by wound healing migration assays.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, they developed a further series of Ir III complexes ( 66 – 69 , Scheme ) containing benzimidazole groups for lysosome‐targeted PDT . These complexes showed much higher singlet‐oxygen quantum yields in acidic solution (pH 5.4) than in neutral solution.…”
Section: Organelle‐specific Iriii Complexesmentioning
confidence: 99%
“…The highest PI achieved was >476 for 69 in HeLa cells, with almost no dark toxicity. Complex 69 can also inhibit tumor growth effectively in nude mice in vivo after photodynamic therapy . An in vitro assay against 70 kinases indicated that maternal embryonic leucine zipper kinase (MELK), phosphoinositide‐3‐kinase regulatory subunit 1 (PIK3CA/PIK3R1 (p110 α/p85 α)), and AMP‐activated protein kinase (AMPK A2/B1/G1) were among the most likely three possible molecular targets.…”
Section: Organelle‐specific Iriii Complexesmentioning
confidence: 99%
“…76,77 In last years, the preclinical toxicity of variety of metal complexes (Ag, Au, Ir, Os, Pt, Ru, etc.) has been tested in the zebrafish embryos, [78][79][80][81] while, to the best of our knowledge, only one study explored Re(I) tricarbonyl complexes in this model. 51 Herein, according to the determined LC50 values ( were compared to those in the control (DMSO-treated) group and the groups treated with clinically approved drugs -cisplatin, doxorubicin and sunitinib-malate.…”
Section: In Vivo Toxicity Assessment and Therapeutic Potential Determmentioning
confidence: 99%